Wind Speed Distributions Used in Wind Energy Assessment: A Review - Shi, Huanyu; Dong, Zhibao; Xiao, Nan; Huang, Qinni (Frontiers in Energy Research, 2021)
With economic development and population growth, energy demand has shown an upward trend. Renewable energy is inexhaustible and causes little pollution, which has broad prospects for development. In recent years, wind energy has been developed as an essential renewable energy source. The use of wind power is very environmentally friendly and plays a critical role in economic growth. Assessing the characteristics and potential of wind energy is the first step in the effective development of wind energy. The wind speed distribution at a specific location determines the available wind energy. This paper reviews the wind speed distribution models used for wind energy assessment, and they are applicable to different wind regimes. All potential wind speed distribution models should be considered for modeling wind speed data at a particular site. Previous studies have selected several parameter estimation methods and evaluation criteria to estimate model parameters and evaluate the goodness-of-fit. This paper discusses their advantages and disadvantages. The characteristics of wind speed distribution are constantly varying geographically and temporally. Wind energy assessment should consider local geographical elements, such as local climate, topography, and thermal properties difference between the land and the sea, and focus on long-term variations in wind characteristics.